Development of a Nutrition Care Process implementation package for hospital dietetic departments. Issue 3 (20th March 2015) - Porter, Jane M.; Devine, Amanda; Vivanti, Angela; Ferguson, Maree; O'Sullivan, Therese A.
Abstract Aim The Academy of Nutrition and Dietetics has led the development and dissemination of the Nutrition Care Process (NCP), incorporating the Nutrition Care Process Terminology as the standardised language. This research investigates and compares the views of Australian dietitians pre and post NCP implementation to inform development of an NCP implementation package. Methods Dietitians from two hospitals that had undergone informal NCP implementation (post‐implementers, n = 35) and three hospitals yet to implement NCP (pre‐implementers, n = 35) completed an online questionnaire (ASK NCP) surveying demographics and constructs relating to knowledge, familiarity, confidence, support, value, barriers, training and NCP education. Results Post‐implementers had higher knowledge scores (P < 0.05), were more familiar with NCP (P < 0.01), confident to implement (P < 0.01) and supported to use NCP (P < 0.01) than pre‐implementers. Lack of knowledge, support, training and resources was identified as a barrier by pre‐implementers. Busy workloads and work status were identified as barriers by post‐implementers. Pre‐implementers felt they had insufficient NCP training; however, if further training and support were to be provided, almost all reported they would be more confident to implement. Keys to successful implementation included allocated time to practice and regular tutorials; support and leadership from their management and NCP department leader; and professional growth through understanding how change could benefit practice. Conclusions The results of the study were used to inform the development of an NCP implementation package. Kotter's eight stages of change were identified as the most appropriate change management model with the framework incorporated into the package development.